Specialty training in Medicine - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2019)
Medical service is unconditional act with good faith that doesn’t always follow the theory of economics and business. Specialty training is must and sub-specialty is the demand of time. Medical education and trainings are delivered according to the desired target within the defined territory.